2018
DOI: 10.1093/nar/gky1027
|View full text |Cite
|
Sign up to set email alerts
|

EWAS Atlas: a curated knowledgebase of epigenome-wide association studies

Abstract: Epigenome-Wide Association Study (EWAS) has become increasingly significant in identifying the associations between epigenetic variations and different biological traits. In this study, we develop EWAS Atlas (http://bigd.big.ac.cn/ewas), a curated knowledgebase of EWAS that provides a comprehensive collection of EWAS knowledge. Unlike extant data-oriented epigenetic resources, EWAS Atlas features manual curation of EWAS knowledge from extensive publications. In the current implementation, EWAS Atlas focuses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
200
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(222 citation statements)
references
References 30 publications
2
200
0
Order By: Relevance
“…EWAS is based on linkage disequilibrium (LD) mapping, which utilizes natural population and historic recombination events and thus can accomplish high-resolution mapping. A number of EWAS studies have been conducted in humans, which identified that epigenetic modifications are associated with several human diseases like Parkinson's disease [84], coronary artery disease [85], Alzheimer's disease [86] and Type 2 diabetes [87], Moreover, to gather the extensive knowledge generated through EWAS in human, EWAS Atlas has also been developed [88]. However, there is a limited number of EWAS performed in plants, and so far, a single EWAS study identified epigenetic modification associated with a mantled abnormality in oil palm [44].…”
Section: Epiqtls and Epigenome-wide Association Study (Ewas)mentioning
confidence: 99%
“…EWAS is based on linkage disequilibrium (LD) mapping, which utilizes natural population and historic recombination events and thus can accomplish high-resolution mapping. A number of EWAS studies have been conducted in humans, which identified that epigenetic modifications are associated with several human diseases like Parkinson's disease [84], coronary artery disease [85], Alzheimer's disease [86] and Type 2 diabetes [87], Moreover, to gather the extensive knowledge generated through EWAS in human, EWAS Atlas has also been developed [88]. However, there is a limited number of EWAS performed in plants, and so far, a single EWAS study identified epigenetic modification associated with a mantled abnormality in oil palm [44].…”
Section: Epiqtls and Epigenome-wide Association Study (Ewas)mentioning
confidence: 99%
“…EWAS opens the door for researchers to study complex diseases, allowing us to find several previously undiscovered disease-related methylation sites, providing more epigenetic mechanisms for the pathogenesis of complex diseases [12,13]. Since 2009 when the first EWAS study was published, EWAS research has grown exponentially in recent years, reaching 618 publications in 2019 [12]. Due to the availability of whole blood DNA methylation data, most of the materials for most current EWAS studies are focused on whole blood tissues [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to GWAS (Genome-wide association study), EWAS compares the variation between patients and healthy people at the DNA methylation level and associates epigenetic variation with complex diseases as well as interprets the pathogenic cause of complex diseases at the epigenetic level [11]. EWAS opens the door for researchers to study complex diseases, allowing us to find several previously undiscovered disease-related methylation sites, providing more epigenetic mechanisms for the pathogenesis of complex diseases [12,13]. Since 2009 when the first EWAS study was published, EWAS research has grown exponentially in recent years, reaching 618 publications in 2019 [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EWAS model selects CpG sites that are easily affected by environmental factors through screening a large number of CpG sites. Standard EWAS generally uses whole blood data, which means the value of methylation data contains information on heterogeneous cell composition [4,5]. Existing research has shown that epigenome information is greatly affected by cell changes.…”
Section: Background Introductionmentioning
confidence: 99%